A Comparative Study Of Different Collectors In The Flotation Of Rare Earth Mineral - Muhamad Azman, Nadiah Adlin (Universiti Sains Malaysia, 2022)
Application of rare earth elements (REE) in various filed had caused the demand for REE-bearing minerals (REM) to spike in these recent years. Xenotime (YPO4), a source of yttrium (Y) is often sought for its high-temperature superconductors properties and also as an additive in alloys. Froth flotation as a fundamental method for processing complex minerals is commonly applied in the beneficiation of rare-earth-bearing minerals. This research program was designed to compare the effectiveness between two different collectors (octano-hydroxamic acid and sodium oleate) and its concentration on xenotime flotability. The froth flotation study is carried out using bench flotation equipment with the condition of pH 7 and at room temperature. Samples were also characterized using Particle Size Analysis (PSA), X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and Scanning Electron Microscopy (SEM). In the absence of depressant, octano-hydroxamic acid shows better selectivity in the flotation of xenotime than sodium oleate. On the other hand, sodium oleate produces better grade of xenotime with the presence of depressant. Increases in concentration will improve xenotime grade but at higher concentration it can be detrimental. Optimum concentration for xenotime flotation was found at 0.001M. Overall, the addition of sodium silicate as depressant can significantly increase xenotime grade and successfully depress silica and alumina. However, it shows no depressing power on hematite. The knowledge gained from this work will be beneficial in selecting appropriate collectors for xenotime recovery in the industry.